MEDIA PENDIDIKAN (Seri Tafsir Tarbawi) - Muliati, Binti (Jurnal al Hikmah, 2018)
The life of the human race is inseparable from education. Education is very important for Islamic humanity. As a prospective educator, of course it is expected to be a professional educator. In the Qur'an, it has been explained how to be a good and professional teacher or educator. Talking about education is certainly inseparable from the name of the media. There are several verses in the quran which discuss the media of education. This article will briefly discuss the verses about educational media according to the Qur'an